2013
DOI: 10.4018/jeco.2013010101
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Consumers’ High and Low Trust as Constructs for Predicting Online Shopping Behavior

Abstract: This research examines the constructs of high and low trust on consumers’ behavior with online shopping. The authors developed a research model and instrument to study the trust construct in the acceptance online shopping applications. The authors hypothesized that trust positively influences a person’s intention to purchase from a virtual store and that trust positively affects the consumer’s attitude toward using the e-store. Consumers who trust an online company feel more committed to it. Previous research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…High convenience, when ease of use is low, was not intuitive; however, our analysis found that "perceived" convenience may offset the difficulties in the ease of use. Trust was found to be a key variable in the research by Amoroso and Mukahi (2010) in the buildup of inertia for increase in the adoption of technologies.…”
Section: Figure 1 Amoroso and Ogawa (2011) Mobile Adoption Modelmentioning
confidence: 99%
“…High convenience, when ease of use is low, was not intuitive; however, our analysis found that "perceived" convenience may offset the difficulties in the ease of use. Trust was found to be a key variable in the research by Amoroso and Mukahi (2010) in the buildup of inertia for increase in the adoption of technologies.…”
Section: Figure 1 Amoroso and Ogawa (2011) Mobile Adoption Modelmentioning
confidence: 99%
“…A variation of trust is trustworthiness, the qualitative level of trust perceived by others in a person. (Wilson & Eckel 2010;Amoroso & Mukahi 2013;Fleming et al 2014). In the IS literature, reciprocity and trust are forms of relational social capital; trust covaries with reciprocity to lead to higher volume and quality of knowledge sharing in virtual communities (Chiu et al 2006).…”
Section: Reciprocity and Trustmentioning
confidence: 99%
“…In the pasaload context trust is an important antecedent of reciprocity: before exchanges can occur, there must be a modicum of trust between senders and receivers of prepaid loads. Amoroso & Mukahi (2013) found that a consumer's propensity to trust leads to increased loyalty among persons trusting and being trusted. Therefore, we hypothesize that: H2a: Trust is positively correlated with Loyalty.…”
Section: Trust and Loyaltymentioning
confidence: 99%
“…For example, Hoffman et al (1999) concluded that around 95% of website users refrained from providing requested personal data on one or more occasions and that 69% of those who refused to provide the data did so because the businesses failed to provide information on how said data would be used. Furthermore, even when businesses adopt encryption practices to ensure data confidentiality and security during a transaction (Secure Sockets Layer -SSL and Secure Electronic Transaction -SET), a part of potential customers refrain from using digital banking services (Luarn & Lin, 2004), which suggests that the greatest problem does not lie in objective security conditions, but rather in subjective psychological factors (Amoroso & Mukahi, 2013;Grabner-Krauter & Bitter, 2015;Hsiao, 2009;Kim et al, 2008;Nguyen et al, 2018;Oliveira et al, 2017).…”
Section: Introductionmentioning
confidence: 99%